Public-Private Partnerships in Technical and Vocational Education and Training (TVET): Strengthening Skill Ecosystems and Labour Market Integration - Olaide David Adeleye; Samson Joshua Salasi; Taiwo Grace Wale-Fadairo (Journal of Business and Digital Innovation, 2026)
This study empirically examines the role played by Public-Private Partnerships (PPPs) in the relevancy, quality and labour market performance of Technical and Vocational Education and Training (TVET) programmes in Nigeria. Quantitative data were gathered on the first stage using an explanatory sequential mixed methods design, where 180 respondents (graduates, employers and institutional administrators) in Lagos, Ogun and Kaduna States were surveyed. These data evaluated PPP typologies, curriculum alignment, and employment outcomes. The second stage involved the implementation of qualitative interviews and focus group discussions (n = 28) and the explanation and contextualisation of the quantitative results. It is shown in the quantitative data that the PPP supported institutions are more aligned to the needs of the industry in the curriculum and have higher rates of graduate employment 6 months (65 percent) in relation to traditional public TVET institutions (47 percent). The results of the logistic regression indicate that the participation in PPP strongly predicts employment results (p < 0.05). Qualitative results indicate that these better outcomes are attributed to curriculum co design, structured workplace learning, and employer engagement mechanisms, and are limited by policy fragmentation and weak financing frameworks. The study concludes that PPPs have the capacity to enhance TVET skill ecosystem in cases where institutional alignment and governance frameworks are well spelt out. The policy suggestions are regulatory harmonisation, a combination of funding, and a systematic approach to employer involvement in the process to enhance scalable and inclusive TVET provision.